Uncompleted Emergency Department Care (UEDC): a 5-year population-based study in the Veneto Region, Italy - SAIA, M. (J Prev Med Hyg, 2019)
INTRODUCTION: Uncompleted visits to emergency departments (UEDC) are a patient safety concern. The purpose of this study was to investigate risk factors for UEDC, describing not only the sociodemographic characteristics of patients who left against medical advice (AMA) and those who left without being seen (LWBS), but also the characteristics of their access to the emergency department (ED) and of the hospital structure. METHODS: This was a cross sectional study on anonymized administrative data in a population-based ED database. RESULTS: A total of 9,147,415 patients attended EDs in the Veneto Region from 2011 to 2015. The UEDC rate was 28.7‰, with a slightly higher rate of AMA than of LWBS (15.3‰ vs 13.4‰). Age, sex, citizenship, and residence were sociodemographic factors associated with UEDC, and so were certain characteristics of access, such as mode of admission, type of referral, emergency level, waiting time before being seen, and type of medical issue (trauma or other). Some characteristics of the hospital structure, such as the type of hospital and the volume of patients managed, could also be associated with UEDC. CONCLUSION: Cases of UEDC, which may involve patients who leave AMA and those who LWBS, differ considerably from other cases managed at the ED. The present findings are important for the purpose of planning and staffing health services. Decision-makers should identify and target the factors associated with UEDC to minimize walkouts from public hospital EDs.